Extracorporeal cellular therapy (ELAD) in severe alcoholic hepatitis: A multinational, prospective, controlled, randomized trial. Issue 3 (23rd February 2018) - Thompson, Julie; Jones, Natasha; Al‐Khafaji, Ali; Malik, Shahid; Reich, David; Munoz, Santiago; MacNicholas, Ross; Hassanein, Tarek; Teperman, Lewis; Stein, Lance; Duarte‐Rojo, Andrés; Malik, Raza; et al.
Abstract : Severe alcoholic hepatitis (sAH) is associated with a poor prognosis. There is no proven effective treatment for sAH, which is why early transplantation has been increasingly discussed. Hepatoblastoma‐derived C3A cells express anti‐inflammatory proteins and growth factors and were tested in an extracorporeal cellular therapy (ELAD) study to establish their effect on survival for subjects with sAH. Adults with sAH, bilirubin ≥8 mg/dL, Maddrey's discriminant function ≥ 32, and Model for End‐Stage Liver Disease (MELD) score ≤ 35 were randomized to receive standard of care (SOC) only or 3‐5 days of continuous ELAD treatment plus SOC. After a minimum follow‐up of 91 days, overall survival (OS) was assessed by using a Kaplan‐Meier survival analysis. A total of 203 subjects were enrolled (96 ELAD and 107 SOC) at 40 sites worldwide. Comparison of baseline characteristics showed no significant differences between groups and within subgroups. There was no significant difference in serious adverse events between the 2 groups. In an analysis of the intent‐to‐treat population, there was no difference in OS (51.0% versus 49.5%). The study failed its primary and secondary end point in a population with sAH and with a MELD ranging from 18 to 35 and no upper age limit. In the prespecified analysis of subjects with MELD < 28 (n = 120), ELAD was associated with a trend toward higher OS at 91 days (68.6% versus 53.6%; P  = .08). Regression analysis identified high creatinine and international normalized ratio, but not bilirubin, as the MELD components predicting negative outcomes with ELAD. A new trial investigating a potential benefit of ELAD in younger subjects with sufficient renal function and less severe coagulopathy has been initiated. Liver Transplantation 24 380–393 2018 AASLD.